Andean elevation control on tropical Pacific climate and ENSO. (11th August 2014) - Feng, Ran; Poulsen, Christopher J.
Abstract Late Cenozoic marine proxy data record a long‐term transition in the tropical Pacific from El Niño‐like conditions with reduced zonal sea surface temperature (SST) gradient, deepened thermocline, and reduced upwelling in the eastern equatorial Pacific (EEP) to conditions similar to modern. This transition coincides with kilometer‐scale uplift of the central Andes. To understand whether the rise of the Andes contributed to tropical Pacific climate evolution, we performed experiments with the National Center for Atmospheric Research's Community Climate System Model version 4 to quantify changes in tropical Pacific climate and El Niño–Southern Oscillation as a function of Andean elevations. Our results demonstrate that uplift increases the equatorial east‐west SST gradient and Walker circulation. The rise of the Andes from 1 to 3 km increases the SST gradient by 0.8°C and Walker circulation by 60% due to strengthened radiative cooling by enhanced low‐cloud formation in the EEP. This cooling effect is largest in the southeastern tropical Pacific and accounts for about one half of the reconstructed SST cooling along the Peru coast. The uplift also strengthens upwelling north of the EEP, consistent with documented increases in biological productivity in this region, and decreases the frequency of El Niño–Southern Oscillation and the number of strong El Niño events. Simulated responses to Andean uplift are generally consistent with the late Cenozoic proxy records, but too small in magnitude. Taken together, our results indicate that Andean uplift was likely one of the multiple factors that contributed to the long‐term evolution of both the mean climate state and the interannual variability in the tropical Pacific.